Structural Design of Blocking Element of Magnetic Cycloid Transmission - Bezák, Juraj; Bezák, Peter; Vajdová, Alena (Manufacturing Technology Journal, 2015)
The contribution deals with the study of magnetic structures, computational methods used in analyzing the interaction of magnetic fields with application this knowledge in practice.The main object of study is design of blocking element of magnetic cycloid gearbox. This paper describes the design methodology of magnetic blocking element, calculation of the braking system, the maximum breakaway torque at slipping in magnetic coupling and power ratios during this action.
Keywords: blocking element; stress analysis; visualization